2018
DOI: 10.1101/452243
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of SATB1 Induces a p21 Dependent Cellular Senescence Phenotype in Dopaminergic Neurons

Abstract: Cellular senescence is a mechanism used by mitotic cells to prevent uncontrolled cell division. As senescent cells persist in tissues, they cause local inflammation and are harmful to surrounding cells, contributing to aging. Generally, neurodegenerative diseases, such as Parkinson's, are disorders of aging. The contribution of cellular senescence to neurodegeneration is still unclear. SATB1 is a DNA binding protein associated with Parkinson's disease. We report that SATB1 prevents cellular senescence in post-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 71 publications
3
9
0
Order By: Relevance
“…Nevertheless, a neuronal SASP is supported by other observations, such as the induction of expression of pro-inflammatory cytokines like TNF-α and CCL2 [33]. Interestingly, dopaminergic neurons with senescent phenotype due to lack of expression of SATB1, a DNA binding protein reduced in the vulnerable region of Parkinson´s Disease patients, express several SASP components, including MCP-1 [34], the cytokine we found significantly secreted by senescent cortical cells. MCP-1 is also secreted by senescent human mesenchymal stem cells and induces paracrine senescence; according to our findings, MCP-1 expression is mediated by GATA4 [28], a transcription factor we found increased in senescent cortical neurons.…”
Section: Discussionsupporting
confidence: 62%
“…Nevertheless, a neuronal SASP is supported by other observations, such as the induction of expression of pro-inflammatory cytokines like TNF-α and CCL2 [33]. Interestingly, dopaminergic neurons with senescent phenotype due to lack of expression of SATB1, a DNA binding protein reduced in the vulnerable region of Parkinson´s Disease patients, express several SASP components, including MCP-1 [34], the cytokine we found significantly secreted by senescent cortical cells. MCP-1 is also secreted by senescent human mesenchymal stem cells and induces paracrine senescence; according to our findings, MCP-1 expression is mediated by GATA4 [28], a transcription factor we found increased in senescent cortical neurons.…”
Section: Discussionsupporting
confidence: 62%
“…We have recently reported that NURR1 (NR4A2) can serve as a reliable marker of early post-mitotic mDA neurons under floor-plate differentiation conditions. An NURR1:H2B-GFP reporter line allowed enrichment of mDA neurons in vitro that yielded nearly pure populations based on mDA markers such as FOXA2, LMX1A, NURR1 and TH including by using flow based and sc-RT-qPCR analyses (Riessland et al, 2019). While genetic engineering and FACS-based purification of neurons presents major challenges of human translation, it may be possible to adapt this approach for MACS-based or genetic selection strategies more suitable or translation.…”
Section: Homogenous Mda Cell Populationmentioning
confidence: 99%
“…To examine the impact of SARS-CoV-2 infection on DA neurons, Nurr1:GFP reporter hPSCs were differentiated toward a DA neuron fate using a previously established strategy 8,9 . The resulting DA neurons were validated by the expression of Nurr1:GFP, TH, and FOXA2 (Extended Data Fig.…”
Section: Main Textmentioning
confidence: 99%